Inelastic torsional buckling of simple three-dimensional moment resisting frame - Fukuda, Iori; Ikago, Kohju; Araki, Yoshikazu; Wagg, David J. (Frontiers in Built Environment, 2024)
Recent massive earthquakes have raised concerns that megathrust earthquakes with magnitude 9 can occur in the near future. This paper discusses critical behavior of structures involving torsion caused by extreme ground motions. Unlike factors such as mass and stiffness eccentricity and accidental torsion in a structure that induce torsion, torsional buckling can occur in a moment-resisting frame (MRF) when all beam ends in the longitudinal and transverse directions yield in the lower stories, even if the frame is well designed and its eccentricity is negligibly small. In this study, the theoretically predicted buckling load was presented and validated via numerical analyses. This paper shows that excluding P-Delta effect resulted not only in underestimated deformation but also in overlooked torsional buckling. This study suggests that a high-rise MRF designed in accordance with modern seismic design codes can suffer torsional collapse when the beam ends of the lower stories yield owing to extreme ground motion. Based on these findings, we recommend considering the P-Delta effect when examining critical behavior of high-rise buildings not to overlook the brittle failure mode.